Grand Design of Village-Based Islamic Economic Development Planning in an Effort to Achieve Sustainable Development of Indonesia Gold 2045 in Ngancar village, Plaosan district, Magetan Regency - Kusnul Ciptanila Yuni K; Mohamad Nur Efendi; Athi’ Hidayati (Universitas Darussalam Gontor, 2023)
Welcoming the rise of Indonesia's golden generation in 2045, it is necessary to develop a populist economy in a future perspective, namely creating a quality, advanced, independent and modern Indonesian society, as well as increasing the nation's dignity. The success of the village through Ngancar village, Plaosan District, Magetan Regency in developing the economy will make a major contribution to achieving overall national development goals. This research is a field research with a qualitative approach. Sources of data in this study using secondary data derived from books and relevant research results. The findings of this study basically want to explore the practices of Ngancar village in the areas of food security, local economy, utilization of renewable energy, education, sanitation/health, use of information technology, and democratic involvement. The purpose of this research is to analyze the possibility of community-based economy (populist economy) implementation in Malang district to achieve sustainable economic development. In this research, there are four design stages based on the populist economy: first, mapping of leading economic sectors in Malang Regency. Second, mapping the socio-political conditions surrounding the community. Third, identify the existing institutional arrangements. Fourth, designing an appropriate form of partnership to accommodate the common interests of the government, private sector and the community in the perspective of As-Syatibi Islamic economic development.